Individuals' perceptions of their lifestyles, personal hygiene and anxiety after the COVID-19 pandemic (Annals of Medical Research, 2023)
Aim: COVID is a life-threatening pandemic disease that can lead to panic-attack disorder, anxiety, mourning, loss and depression. However, it is thought that it may negatively affect their lifestyle, personal hygiene and perception of anxiety. In this direction, the aim of the study is to examine the lifestyle, personal hygiene and anxiety perceptions of individuals after the COVID-19 pandemic.Materials and Methods: In the study, a 12-item questionnaire was applied to determine the perceptions of individuals about their lifestyle, personal hygiene and concerns after the epidemic. The questionnaire was applied via the internet and the data collected is limited to the responses of participants. Data was collected from a total of 2003 social media users from different provinces using convenience sampling.Results: In the study, it was thought that the participants would significantly change their lifestyles after COVID-19. Accordingly, while online shopping has increased relatively, behavioral changes regarding active living spaces have also developed.Conclusion: According to the data in the study, significant changes are expected in the lifestyles of societies after the COVID-19 pandemic. New lifestyles, marked by moving away from crowds, will transform consumer styles. In this direction, it seems inevitable to create new policies for various social areas such as entertainment world, tourism, food and beverage sector, transportation, architecture and shopping.
Keywords: COVID-19; Lifestyle; Anxiety; Personal hygiene